2021
DOI: 10.1186/s12882-021-02468-x
|View full text |Cite
|
Sign up to set email alerts
|

Renal recipients’ knowledge and self-efficacy during first year after implementing an evidence based educational intervention as routine care at the transplantation clinic

Abstract: Background Following an implementation plan based on dynamic dialogue between researchers and clinicians, this study implemented an evidence-based patient education program (tested in an RCT) into routine care at a clinical transplant center. The aim of this study was to investigate renal recipients’ knowledge and self-efficacy during first year the after the intervention was provided in an everyday life setting. Methods The study has a longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…For example, for patients with low education levels, they can conduct propaganda and education through pictures, videos and other easy to understand ways, and regularly give feedback or carry out patient exchanges (27). Patients with high knowledge scores can share their own life habits, spread knowledge, and obtain positive stimulation among patients, so as to improve the knowledge level of kidney transplantation (13,28). This study shows that patients who have received health education have a higher level of knowledge about kidney transplantation, which is consistent with the study.…”
Section: Kang Et Al (10 23mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for patients with low education levels, they can conduct propaganda and education through pictures, videos and other easy to understand ways, and regularly give feedback or carry out patient exchanges (27). Patients with high knowledge scores can share their own life habits, spread knowledge, and obtain positive stimulation among patients, so as to improve the knowledge level of kidney transplantation (13,28). This study shows that patients who have received health education have a higher level of knowledge about kidney transplantation, which is consistent with the study.…”
Section: Kang Et Al (10 23mentioning
confidence: 99%
“…Studies had shown that the lack of transplant-related knowledge in KT candidates could cause preoperative anxiety, fear and lack of mental preparation for the postoperative situation (11,12). For KT recipients, lack of transplant related knowledge would lead to postoperative infection, and even death in severe cases (13).…”
mentioning
confidence: 99%
“…Service provision for supporting self-management could be developed further to include patient education programmes [ 7 , 15 ] to enable patients to acquire skills related to medical management and to educate about how to live a full life with illness [ 15 ]. Across European contexts, interventions have been developed to evidence the utility of post-transplant patient education (some combining increasing informational needs with SM skills) [ 7 , 16 , 17 ], despite the evidence that increased graft survival may be a result of improved immunosuppression, management of comorbidities, and education of patients [ 18 ]. Nurses have a key role in interacting with, educating, and supporting this group of patients to maximise independence in patients initiating their own care ([ 18 ]).…”
Section: Introductionmentioning
confidence: 99%
“…However, since patients after KT need to take immunosuppressants for life, and strictly follow the doctor's advice to implement life management, diet management, etc., it is necessary to ensure that patients master scientific knowledge related to KT (Cheng, 2020 ). Lack of relevant knowledge may lead to rejection and graft failure (Andersen et al, 2019 ; Maasdam et al, 2022 ; Urstad et al, 2021 ). For the KT candidates, patients will be nervous and afraid because of worries about the effect of transplantation or have too many expectations about transplantation, and lack of ideological preparation for the infection and complications (Wu, 2016 ).…”
Section: Introductionmentioning
confidence: 99%